PENGARUH PROSEDUR REKRUTMEN, DAYA TARIK LINGKUNGAN KERJA FISIK, DAN DAYA TARIK KOMPENSASI TERHADAP MOTIVASI PELAMAR “OPERATOR” PADA PT PAN BROTHERS TBK & GROUP - Arin Sweiteniasari; Rara Ririn Budi Utami; Jumi Jumi (Politeknik Negeri Semarang, 2016)
This study aims to analyze the influence of recruitment procedures, the appeal of physical working environment, and the appeal of compensation toward motivate job applicants operator PT Pan Brothers Tbk and Group. The data that were used was primary data from 100 respondents, which were analyzed using multiple linear regression analysis to estimate the influential factors. According to data analysis result, the multiple linear regression was Y = 12.665 + 0.384 X1 + 0.458 X2 + 0.313 X3, the coefficient of F test = 0.000 (<0.05), which means that all independent variables simultaneously had significant influence toward dependent variable. This research used 5% significant level, the coefficient of T test for the recruitment procedure (X1) = 0.011, physical work environment (X2) = 0.008, and compensation (X3) = 0.038, the significant value for all independent variables < 0.05, it means that the recruitment procedures, the physical working environment, and compensation partially has significant effect toward the motivation of job applicants operator. While the Determination Coefficient (Adjusted R2) = 0337, or 33.7%, it means that the recruitment procedure (X1), physical work environtment (X2), and compensation (X3) contributed 33.7 % to the motivation of job applicants operator (Y), while the remaining 66.3% were determined by other variables not examined in this study.